Seasonal Dynamics in Carbon Cycling of Marine Bacterioplankton Are Lifestyle Dependent - Martínez-García, Sandra; Bunse, Carina; Pontiller, Benjamin; Baltar, Federico; Israelsson, Stina; Fridolfsson, Emil; Lindh, Markus V.; Lundin, Daniel; Legrand, Catherine; Pinhassi, Jarone (Frontiers in Microbiology, 2022)
Although free-living (FL) and particle-attached (PA) bacteria are recognized as ecologically distinct compartments of marine microbial food-webs, few, if any, studies have determined their dynamics in abundance, function (production, respiration and substrate utilization) and taxonomy over a yearly cycle. In the Baltic Sea, abundance and production of PA bacteria (defined as the size-fraction >3.0 µm) peaked over three months in summer (six months for FL bacteria), largely coinciding with blooms of Chitinophagales (Bacteroidetes). Pronounced changes in the growth efficiency (range 0.05-0.27) of FL bacteria (defined as the size-fraction <3.0 µm) indicated the magnitude of seasonal variability of ecological settings bacteria experience. Accordingly, 16S rRNA gene analyses of bacterial community composition uncovered distinct correlations between taxa, environmental variables and metabolisms, including Firmicutes associated with elevated hydrolytic enzyme activity in winter and Verrucomicrobia with utilization of algal-derived substrates during summer. Further, our results suggested a substrate-controlled succession in the PA fraction, from Bacteroidetes using polymers to Actinobacteria and Betaproteobacteria using monomers across the spring to autumn phytoplankton bloom transition. Collectively, our findings emphasize pronounced seasonal changes in both the composition of the bacterial community in the PA and FL size fractions and their contribution to organic matter utilization and carbon cycling. This is important for interpreting microbial ecosystem function-responses to natural and human-induced environmental changes.